PERLINDUNGAN HUKUM PARA PIHAK SEBAGAI PEMEGANG KOMPONEN PESAWAT UDARA SEBAGAI JAMINAN HUTANG SECARA FIDUSIA DALAM PERJANJIAN KREDIT DALAM RANGKA PENGEMBANGAN INDUSTRI PENERBANGAN - Pradnya Paramitha Dias Rahmadhani; Mochammad Najib Imanullah (Jurnal Privat Law, 2021)
AbstractThe purpose of this study is to know about the legal protection the parties as components of aircraft components as collateral for fiduciary debt in credit agreements in the context of developing the aviation industry.This research is a normative law research which is descriptive. It used statute approach and comparative approach. The materials used in the research are primer law material and secondary law material by using library research as the data collection technique. In analyzing the law material, the researcher used the method of syllogism deduction to explain the general things to draw the specific conclusion. Based on the result it can be concluded that the importance of legal certainty of aircraft as a guarantee as collateral for credit agreements in the development of the aviation industry , because many uses of aircraft in this era so that special regulations are needed about the legal certainty of aircraft as a guarantee as collateral for credit agreements in the development of the aviation industry.